Islamic Religious Education Strategy Based on Multiple Intelligences - Junaidi (Newinera Publisher, 2025)
This study examines the implementation of Multiple Intelligences (MI)-based strategies in Islamic Religious Education (PAI) at MTs Al-Ittihadiyah Pekanbaru, focusing on how these strategies address student heterogeneity in learning abilities, styles, and motivations. Using a qualitative case study approach, data were collected through observations, interviews, and documentation to explore the planning, implementation, and evaluation of MI-based PAI learning. The findings reveal that MI-oriented strategies enhance student engagement and comprehension by aligning instructional activities with diverse intelligence profiles, including linguistic, logical, interpersonal, kinesthetic, and visual-spatial strengths. The study also highlights the importance of teacher competence, technology integration, and contextualized curriculum design in supporting effective MI implementation. Despite challenges such as limited facilities and partial teacher readiness, the use of MI-based strategies contributes positively to both cognitive and affective learning outcomes. The study concludes that MI-based pedagogy offers a promising and relevant approach to improving the quality of Islamic education in contemporary madrasah settings and recommends stronger institutional support and ongoing professional development for educators.